2016
DOI: 10.1590/s0100-204x2016000500009
|View full text |Cite
|
Sign up to set email alerts
|

Interceptações de pragas quarentenárias e ausentes não regulamentadas em material vegetal importado

Abstract: Resumo -O objetivo deste trabalho foi avaliar as informações qualitativas e quantitativas sobre as interceptações de pragas ausentes não regulamentadas e quarentenárias em material vegetal importado. As informações sobre interceptações de pragas pelo serviço de quarentena vegetal da Embrapa, no período de 1977 a 2013, foram obtidas em um banco de dados, atas laboratoriais e listas de interceptação publicadas. As interceptações foram analisadas de acordo com regulamentação das pragas, espécie vegetal, parte veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…According to the Brazilian Ministry of Agriculture, Livestock and Food Supply, five out of the nine species studied here are considered absent quarantine pests: E. maideni , O. postica , S. anale , and T. sloanei . A study compiling information on pest interception in the Brazilian territory between 1977 and 2013 found that more than half of the intercept species (63%) were considered absent non‐regulated species 53 . When only insects were considered, 17% of the intercepted species were non‐regulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Brazilian Ministry of Agriculture, Livestock and Food Supply, five out of the nine species studied here are considered absent quarantine pests: E. maideni , O. postica , S. anale , and T. sloanei . A study compiling information on pest interception in the Brazilian territory between 1977 and 2013 found that more than half of the intercept species (63%) were considered absent non‐regulated species 53 . When only insects were considered, 17% of the intercepted species were non‐regulated.…”
Section: Discussionmentioning
confidence: 99%
“…A study compiling information on pest interception in the Brazilian territory between 1977 and 2013 found that more than half of the intercept species (63%) were considered absent non-regulated species. 53 When only insects were considered, 17% of the intercepted species were non-regulated. These authors conclude that the review of the quarantine list by phytosanitary authorities is an urgent need.…”
Section: Discussionmentioning
confidence: 99%